Mold Resistance of Bamboo after Laccase-Catalyzed Fixation of Lignin Nanoparticles - Marshallanore, Amat; Chin, Suk Fun; Ngieng, Ngui Sing; Mohd Effendi, Wasli; Awang Ahmad Sallehin, Awang Husaini (John Wiley & Sons, 2024)
In this study lignin nanoparticles (LNPs) and iodolignin nanoparticles (ILNPs) were prepared in aqueous medium and subsequently deposited on the bamboo surfaces via laccase catalyzed reaction. The SEM micrographs of blocks treated with LNPs and ILNPs revealed a layer of nanoparticles with a mean particles size of 100 nm and 215 nm. Besides that, the fungal isolates from the bamboo culm of Dendrocalamus asper shared 99 %, 98 % and 100 % similarity with Penicillium sumatrense, Pleosporales and Cunninghamella species. The treatment of ILNPs exhibited maximum biocidal efficacy at 91 % against P. sumatrense, Pleosporales sp. and Cunninghamella sp. After leaching with ultrapure water, LNPs-treated blocks exhibited a reduced biocidal effectiveness with an efficacy of 67 %. In contrast, bamboo treated with ILNPs exhibited a higher level of resistance to decay than LNPs. The reduction in mass of 2 %, 3 %, and 1 % was observed when subjecting P. sumatrense, Cunninghamella, and Pleosporales species to treatment with ILNPs. This study demonstrates the application of laccase catalysis in both LNPs and ILNPs, indicating a potentially effective approach for providing surface protection to bamboo against plant pathogenic fungi.